Cango Lyec (Healing the Elephant): Gender Differences in HIV Infection in Post-conflict Northern Uganda. (1st July 2018) - Spittal, Patricia M.; Malamba, Samuel S.; Ogwang, Martin D.; Musisi, Seggane; Ekwaru, J. Paul; Sewankambo, Nelson K.; Pearce, Margo E.; Jongbloed, Kate; Patel, Sheetal H.; Katamba, Achilles; Blair, Alden H.; Muyinda, Herbert; et al.
Abstract : Background: As previously encamped resettle, potential for rapid HIV transmission in post-conflict Northern Uganda is concerning. Women in particular may be experiencing heightened vulnerability resulting from war-related sexual violence. Setting: Cango Lyec (Healing the Elephant) Project is a cohort involving conflict-affected people in 3 districts in Northern Uganda. Methods: Eight randomly selected communities were mapped, and a census was conducted. Participants aged 13–49 years completed questionnaires in Luo on war-related experiences, mental health, sexual vulnerabilities, and sociodemographics. Blood samples were tested for HIV and syphilis. Baseline data from all sexually active participants was used to determine gender differences in HIV prevalence. Multivariate modeling determined correlates of HIV by gender. Results: Among 2008 participants, HIV prevalence was higher among women [17.2; 95% confidence interval (CI): 14.7 to 19.7] compared to men (10.6; 95% CI: 8.0 to 13.2, <0.001). Among women, correlates of HIV included: war-related sexual assault [adjusted odds ratio (AOR): 1.95; 95% CI: 1.16 to 3.26]; probable depression (AOR: 2.22; 95% CI: 1.46 to 3.37); probable post-traumatic stress disorder (AOR: 2.03; 95% CI: 1.45 to 2.84); experiencing ≥12 traumatic events (AOR: 2.04; 95% CI: 1.31 to 3.18); suicide ideation (AOR: 1.67; 95% CI: 1.22 to 2.28); living in a female-headed household (AOR: 2.76; 95% CI: 1.70 to 4.49); first sexual partner ≥10 years older (AOR: 1.69; 95% CI: 1.07 to 2.67); sex for exchange (AOR: 5.51; 95% CI: 1.76 to 17.31); having 2 (AOR: 2.54; 95% CI: 1.23 to 5.23) or 3+ (AOR: 4.65; 95% CI: 2.65 to 8.18) sexual partners; inconsistent condom use (AOR: 0.40; 95% CI: 0.29 to 0.57); genital ulcers (AOR: 3.08; 95% CI: 2.16 to 4.38); active syphilis (AOR: 4.33; 95% CI: 1.22 to 15.40); and ill health without medical care (AOR: 2.02; 95% CI: 1.22 to 3.34). Among men, correlates of HIV included no condom at sexual debut (AOR: 1.92; 95% CI: 1.30 to 2.83) and genital ulcers (AOR: 4.40; 95% CI: 1.35 to 14.40). Conclusion: Women are disproportionately impacted by HIV, trauma, and depression in this conflict-affected population. Trauma-informed HIV prevention and culturally safe mental health initiatives are urgently required.